# the dipert problem

Posted on September 3, 2012

Recently, Alan Dipert dropped a bomb on the twittersphere with his posing of this question (warning there are spoilers in the replies):

“pop quiz: solve http://www.4clojure.com/problem/107 point-free. answer must be a function value! #clojure”

In case your office has banned 4clojure for being a huge distraction, I’ll post the problem here:

``````(= 256 ((__ 2) 16),
((__ 8) 2))

(= [1 8 27 64] (map (__ 3) [1 2 3 4]))

(= [1 2 4 8 16] (map #((__ %) 2) [0 1 2 3 4]))``````

In problem 107, your challenge is to write a function that satisfies all of these (it could be dropped in place of the `__`s above). I will let you go take a crack at solving it. Because up next is some serious spoiler action.

Got your solution? I came up with this:

``(fn [x] (fn [y] (reduce * (repeat x y))))``

or (what I was really doing) in Haskell:

``````f :: Int -> Int -> Int
f x y = foldl1 (*) (replicate x y)``````

We are doing manual exponentiation: "make a list of ys that is x in length (e.g. `replicate 8 2 == [2, 2, 2, 2, 2, 2, 2, 2]`). Then you just run multiplication through the list:

``foldl1 (*) [2,2,2,2,2,2,2,2] == 2 * 2 * 2 * ... 2 == 256``

Now comes the “Dipert Problem.” He has told us that we have to rewrite the solution (or any solution) using so-called point-free style. I’m sure that there’s more to it, but essentially that means that we are not allowed to mention any variables! When I first heard about this style, it sounded impossible! The cool thing is that it isn’t and it leads to some massively simple code. Let’s try it out.

I’m going to start with my solution above called `f` and then write some successive versions of it, each time, I’ll remove a variable and call it the “next” version: `f1`, `f2`, okay? Cool.

``````f, f1, f2 :: Int -> Int -> Int
f x y = foldl1 (*) (replicate x y)``````

For the first transformation, we need to get rid of the `y` that’s hanging off the end of both sides of our equation. We’ll need to juggle the innards a bit because here is what the types look like so far:

``````foldl1 (*) :: [Int] -> Int
replicate x y :: Int -> a -> [a]``````

`replicate` takes two arguments and then produces a list that the `foldl1 (*)` wants to consume. The trouble is, and what tripped me up a bunch, is that I can’t just do this:

``foldl1 (*) . replicate``

Wah, wah (sad trombone). GHCI tells me:

``````Expected type: Int -> [c0]
Actual type: Int -> a0 -> [a0]``````

Okay, that makes sense, for the fold and replicate to “line up” for composition, replicate has to take one argument then produce a list. The crux is that composition (the “dot” or period in the code) only works for single-argument-functons:

``(.) :: (b -> c) -> (a -> b) -> a -> c``

This is a little pipeline, but reversed because that’s how mathematics does it. It says “the right-side function takes an a and gives a b, and the left-side function expects a b and gives a c; now you can stitch them together and have a function that skips the b and takes you right from a to c.” But we have a function that looks like:

``(a -> b -> c)``

on the right-hand side; it won’t work. how do we convert a `(a -> b -> c)` to a `(a -> (b -> c))`? This way:

``````{-
f x y =  foldl1 (*) ((replicate x) y)
f x y = (foldl1 (*) . (replicate x)) y
-}
f1 x  =  foldl1 (*) . (replicate x)``````

Note: the first two lines are commented in case you are cut-n-pasting along. The first line just puts parenthesis in where they really are in haskell. Each time you see a function of two arguments, it is really a function which takes one argument and returns a function that expects the second argument! This weird but remarkable fact of haskell is called currying.

Now, on to the second line, we see that we have the right types! (I am cheating a bit on types, if you like, you can define `rep` which just uses `Int`s)

``````replicate x :: Int -> [Int]  -- cheating: where 'x' is a specific int
foldl1 (*)  :: [Int] -> Int

foldl1 (*) . replicate x :: Int -> Int``````

And that brings us to `f1`! We used grouping and composition to move the `y` outside the computation and then we dropped it from both sides.

Next we’ll tackle the x:

``````{-
f x =  (foldl1 (*) .) (replicate x)
f x = ((foldl1 (*) .) . replicate) x
-}
f2 =   (foldl1 (*) .) . replicate``````

It may look different, but the same thing is going on. We can group the composition with the fold without changing anything. This is just like doing:

``3 + 4 == (3 +) 4``

Next we do that same trick again where we can now compose the inner functions because the types line up (again, I’m simplifying types a bit):

``((foldl1 (*) .) .) :: (a -> b -> [c]) -> a -> b -> c``

it looks a bit hairy, but in our case, it is just what we want! If I fill in the actual types we’ll be using, it becomes clearer:

``((foldl1 (*) .) .) :: (Int -> Int -> [Int]) -> Int -> Int -> Int``

Booyah! This contraption takes a function of two `Ints` that produces a list of ints, `[Int]`. Well, that’s just what `replicate` is! So if we then feed in replicate:

``(foldl1 (*) .) . replicate :: Int -> Int -> Int``

And that’s it, we have a point-free function that takes two `Int`s and returns an `Int`. And so that’s our last, and final function:

``f2 = (foldl1 (*) .) . replicate``

In general, and I don’t know a term for this, but the operation of successive function composition lets us compose higher and higher arity functions together. Here’s a dumb example using my little point-free `succ` function:

``````g :: Int -> Int
g = (+1)
(g .)       :: (a -> Int) -> a -> Int
(g .) .)    :: (a -> b -> Int) -> a -> b -> Int
(g .) .) .) :: (a -> b -> c -> Int) -> a -> b -> c -> Int``````

Clear pattern. I kinda think of this as saying something like “please give me a function which eventually promises to give me what I want.” The eventually part is essentially “after you’ve collected all the stuff you need.” It would be trivially satisfied by some function that ignores its args and returns a constant:

``(((g .) .) .) (\x y z -> 1) 4 5 6 == 2``

Remembering that `g` just increments, the x y z are totally ignored. The function supplied to the multiply-composed `g` is like some kind of integer “pre-processor”; the x, y and z can be whatever you need to do to figure out how to give g an integer. Or at least that’s how I’m thinking of it.

I had a lot of fun trying to figure this out!